PENINGKATAN KREATIVITAS GURU MELALUI MOTIVASI BERPRESTASI DAN BUDAYA ORGANISASI - Ani Sumarni; Muhamad Entang; Yuyun Elizabeth Patras (JURNAL MANAJEMEN PENDIDIKAN, 2021)
INCREASING TEACHER CREATIVITY THROUGH ACHIEVEMENT MOTIVATION AND ORGANIZATIONAL CULTURETeachers are required to be creative in developing learning activity. This study aimed to find out how teacher creativity has strongly relationships with the achievement motivation and organizational culture. This study was conducted on 134 samples of foundation permanent teachers (GTY) of Integrated Islamic Elementary Schools. They were selected proportionally by using proportional random sampling techniques spread across 9 schools in Tanah Sareal District, Bogor City with a significance level of 0.05. This research was conducted using quantitative methods with correlation techniques. The findings of this study, namely: (1) There was a positive relationship with the level of a strong relationship on achievement motivation (X1) with teacher creativity (Y) with a correlation coefficient (ry1) of 0.7836 and a regression equation Ŷ = 32.539 + 0.730X1; (2) There was a positive relationship with the level of strong relationship in organizational culture (X2) with teacher creativity (Y) with a correlation coefficient (ry2) of 0.6100 and a regression equation Ŷ = 51.915+ 0.520X2; and (3) There was a positive relationship with the level a very strong of relationship in achievement motivation (X1) and organizational culture (X2) together with teacher creativity (Y) with a correlation coefficient (ry12) of 0.8232 and a regression equation Ŷ = 14.787 + 0.594X1 + 0,248X2. Based on these findings, teacher creativity can be enhanced by increasing teacher achievement motivation and school organizational culture as well.